2013
DOI: 10.5901/mjss.2013.v4n11p570
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self-Efficacy, Locus of Control and Academic Performance of Secondary School Students in Ondo State, Nigeria

Abstract: In Nigeria, emphasis has been placed on secondary school students' academic performance because of its direct positive impact on national development. Young students in secondary schools today are expected to be leaders of tomorrow and their academic performance is sine qua non for gaining admission into higher institutions and the quality of manpower the nation can boast of in the future. Unfortunately and generally, secondary school students' academic performance in Nigeria is a serious matter for concern. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
(42 reference statements)
8
16
1
2
Order By: Relevance
“…Consistency in effort instead of total effort was associated with academic achievement [12]. In contrast to [9], [10] and [23] the current study fails to establish associational relationship between self-efficacy and CGPA. No correlation between self-efficacy and locus of control was found in this study which is similar to [20] and [23].…”
Section: Relationship Between Locus Of Control Learning Efforts Selcontrasting
confidence: 96%
See 1 more Smart Citation
“…Consistency in effort instead of total effort was associated with academic achievement [12]. In contrast to [9], [10] and [23] the current study fails to establish associational relationship between self-efficacy and CGPA. No correlation between self-efficacy and locus of control was found in this study which is similar to [20] and [23].…”
Section: Relationship Between Locus Of Control Learning Efforts Selcontrasting
confidence: 96%
“…The current finding supports findings from previous studies in [23] and [21]. Data from the current study also indicate positive association between self-efficacy and learning efforts which is similar to [10] but contradicts [20].…”
Section: Relationship Between Locus Of Control Learning Efforts Selsupporting
confidence: 87%
“…When students are continually bombarded with information and academic tasks by their teachers, the law of diminishing returns gradually set in. Academic burnout, loss of motivation and attention related problems are some of the possible downside of exposing the learners to enormous academic tasks; beyond what they can realistically surmount [17,23]. This finding is in line with the inference drawn by [15] that the length of time spent on instruction has influence on learners' achievement and study habit.…”
Section: Discussionsupporting
confidence: 83%
“…These results was in the same line with [17] who study Academic Self-Efficacy, Locus of Control and Academic Performance of Secondary School Students in Ondo State, Nigeria, they found that locus of control wasn't a good predicator for learning performance. While in contrast with [4] who carried out a study entitled "A Study on Locus of Control and Its Impact on Employee's Performance who reported that internal locus of control was a strong predicator for employee's performance.…”
Section: Discussionsupporting
confidence: 79%
“…It is important to investigate the contributions of psychological skills not only the IQ achievement such as self-locus of control to the prediction of academic performance, whether students have internal or external locus of control as the individuals, who have the internal locus of control, think that they have a big role on affecting the events which influence their lives. Furthermore, they assess themselves as possessing the power for the attitude they want to display by having the positive ego concept, and they believe that they can direct their lives whatever way they desire [17].…”
Section: Discussionmentioning
confidence: 99%